Synthesis and structure of 2, 6-bis(2-methoxyphenyl)dithiazolo[4, 5-b:5′, 4′-e]pyridine) as a novel fluorescent sensor: different recognition of transition metal ions and proton. Issue 3 (20th January 2016) - Darabi, Hossein Reza; Kargar, Maryam; Hajipoor, Roghayeh; Abouali, Negar; Aghapoor, Kioumars; Jadidi, Khosrow; Notash, Behrouz; Sayahi, Hani
Graphical abstract: Abstract: The fluorophore 2, 6-bis(2-methoxyphenyl)dithiazolo[4, 5- b :5′, 4′- e ]pyridine)3, with a planar structure, was synthesized using a one-pot Willgerodt–Kindler reaction which is potentially applicable to various dithiazolopyridines. The basic photophysical characteristics were investigated in organic solvents of different polarity. Chemosensor3 exhibits a 'turn-off' response toward Cu 2+ and Fe 3+ ions, as well as a new emission wavelength-ratiometric response to H + ions, illustrating a different recognition manner. From the binding constant calculations of3 with Cu 2+, increased sensitivity for the fluorescence method over that of the UV–vis method was found, while both methods showed similar sensitivity for binding of3 with H + . On the other hand, the different behavior in the complexes of3 ·H + and3 ·Cu 2+ under cyclic voltammetric analysis was observed. These findings suggest that compound3 may have potential as a sensor for water pollution by Cu 2+ and Fe 3+ ions as well as protons.